THE CONFLICT OF FOREST MANAGEMENT IN KINIPAN: HUMAN RIGHTS, ENVIRONMENTAL PROTECTION, AND THEOLOGICAL PERSPECTIVES - Bimbing Kalvari; Keloso S. Ugak; Idrus Sasirais (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
This study aims to investigate the eco-theological ethical review of the conflict over a customary forest in Kinipan. The method used is qualitative with a phenomenological approach. The study results show that the customary forest conflict in Kinipan is caused by differences in perspectives between the Kinipan community and external parties (government and companies) on the utilization of the forest. The Kinipan community regards the forest as a source of livelihood, cultural sustainability, and happiness, while external parties consider the forest an economic resource. From an ethical perspective, this conflict can be seen as a clash between the collective ethics of the Kinipan community and the individualistic ethics of the external parties. From a theological perspective, this conflict can be seen as a clash between the belief of the Kinipan community in human responsibility to care for nature as a form of obedience to God and the belief of external parties that formal legal power is a source of legitimacy for forest utilization.